Prediction of endotracheal intubation outcome in opioid-poisoned patients: A clinical approach to bispectral monitoring - Eizadi-Mood, Nastaran (Can J Respir Ther, 2014)
BACKGROUND: Some opioid-poisoned patients do not respond appropriately to naloxone; consequently, intubation is required. Although various measures have been used to evaluate the level of consciousness of poisoned patients, no study has assessed the role of the bispectral index (BIS) to ascertain the depth of anesthesia in opioid-poisoned patients who require endotracheal intubation. OBJECTIVE: To compare BIS scores between opioid-poisoned patients with and without intubation, and to determine the BIS cut-off point for endotracheal intubation in these patients. METHODS: In the present cross-sectional study, conducted in an Iranian university referral hospital for poisoning emergencies between 2012 and 2013, opioid-poisoned patients (n=41) were divided into two groups according to their requirement for endotracheal intubation. BIS analyses were performed at the time of admission and at the time of intubation for those who required it. In addition, electromyography and signal quality index were evaluated for all patients at the time of admission, and cardiorespiratory monitoring was performed during the hospitalization period. Using ROC curves, and sensitivity and specificity analyses, the optimal BIS cut-off point for prediction of intubation of these patients was determined. RESULTS: The optimal cut-off point for prediction of intubation was BIS ≤78, which had a sensitivity of 86.7% (95% CI 66.1 to 98.8) and specificity of 88.5% (95% CI 73.9% to 98.8%); the positive and negative predictive values were 81.2 % and 92%, respectively. CONCLUSIONS: BIS may be considered an acceptable index to determine the need for intubation in opioid-poisoned patients whose response to naloxone is inadequate.